Instant Messaging services: a perfect medium to cyber-bullying? - Hanif Suhairi, Abu Bakar; Noormaizatul Akmar, Ishak (Universiti Utara Malaysia (UUM), 2008)
Organized by Universiti Utara Malaysia (UUM), 14th - 16 June 2008 at Corus Hotel, Kuala Lumpur.